Training on Preparing Classroom Action Research Reports for Middle School and High School Teachers - Sumartini, Tina Sri; Afriansyah, Ekasatya Aldila; Asyari, Lutfi; M, Liliek Teja; Fera, Fera; Dedi, Dedi; Hamid, Hamid (Fakultas Kewirausahaan Universitas Garut, 2023)
Teachers must carry out Classroom Action Research (CAR) as an effort to solve problems experienced during learning so that effective solutions are obtained. The results of CAR should be published as a form of accountability for research results and as a reference for determining innovative policies in the field of education. Therefore, it is necessary to conduct training for teachers to publish the results of CAR in national journals. This training is carried out online by providing material and also guidance in the preparation of articles resulting from CAR. The training was attended by 30 teachers in Garut district. The result of this training is that teachers are motivated to make CAR and publish the results in national journals. It is hoped that further training can specifically provide guidance on submitting articles to national journals and can be carried out offline.